Technologies of Fairy-Tale Therapy in the Practice of Psychological Counseling - Stavitskaya, Svetlana Alekseevna (Psychological Prospects Journal, 2012)
The article reveals the peculiarities of using fairy-tale therapy’s methods in the practice of psychological counseling. The author underlines the effectiveness of fairy tale in consultation process with client.
Keywords: fairy-tale therapy diagnostic stage correction stage metaphorical cards